EVALUATION OF NEWER INSECTICIDES FOR THE MANAGEMENT OF MYZUS PERSICAE (SULZER) - naga, kailash chandra (Potato Journal, 2022)
Green peach aphid, Myzus persicae (Sulzer) (Aphididae: Hemiptera) is one of important pest which causes direct and indirect losses to many horticultural crops. To deal with this pest insecticide application remains the principal method to avoid its losses. Therefore, the present study was aimed to evaluate two insecticides with novel mode of action as an alternative to the existing insecticides used for management of M. persicae. Further leaf dip method was followed to evaluate the test chemicals against M. persicae. Probit analysis and LC50 data suggest that flonicamid is as effective as imidacloprid. The flonicamid also has different mode of action and can be used as an alternate chemical to manage M. persicae in potato and other crop ecosystems. This is the first study that indicates insecticidal resistance in M. persicae population in India.